Modelling and Multi-Criteria Analysis of Anaerobic Digestion Process to Get Upgraded Methane from Bio-Residues in the City of Reykjavik - David Christian Finger; Ivana Stepanovic; Tamara Llano (Proceedings, 2019)
Anaerobic digestion of urban organic wastes, farming slurries or sewage sludge is a common practice in waste treatment plants. In the city of Reykjavik, the organic waste fraction constituted by 60% of biomass and 40% of food waste will be transformed by the local waste company SORPA providing biofuel for up to 10% of the cars. Such measures belong to the 2018-2030 Climate Action Plan from the Icelandic Government.